Building Diverse, Distributive, and Territorialized Agrifood Economies to Deliver Sustainability and Food Security. (26th May 2020) - Moragues-Faus, Ana; Marsden, Terry; Adlerová, Barbora; Hausmanová, Tereza
Abstract: This article seeks to understand how agrifood economies can address current sustainability and food security challenges in the context of increasing economic and health inequalities. For that purpose, we cross-fertilize economic geography and food studies literature to develop an innovative conceptual framework that builds upon three currently fragmented bodies of work: the diverse economies literature, the distributed economies framework, and territorial and place-based approaches to food security. The proposed diverse, distributive, and territorial framework further develops existing relational, performative, and spatial approaches to explore changing economic geographies of agrifood systems. The application of this framework to investigate fruit and vegetable provision in the city of Cardiff (UK) reveals the key role of connective, fluid, and multifunctional infrastructures to reconfigure foodscapes. Specifically, our analysis shows how food infrastructures have the potential to act as bridging conceptual, material, and sociopolitical devices. The proposed framework ultimately serves as a capacity-building tool to reassess and rebuild territorialized agrifood economies that champion diversity and redistribution of value with the aim of delivering wide societal and material benefits, enhance democracy, and increase the socioecological resilience of food systems.